Taxonomic comments on Megachile subgenus Chrysosarus (Hymenoptera: Megachilidae) - Gonzalez, Victor H. (Journal of Melittology, 2013)
Comments on the phylogenetic relationships and taxonomy of American leafcutter bees of the genus Megachile subgenus Chrysosarus are provided. The South American subgenera Austrosarus Raw, Stelodides Moure, and Zonomegachile Mitchell are newly synonymized under Chrysosarus Mitchell.